Diagnostic utility of movement disorder society criteria for multiple system atrophy - Zhang, Lingyu; Hou, Yanbing; Wei, Qianqian; Ou, Ruwei; Liu, Kuncheng; Lin, Junyu; Yang, Tianmi; Xiao, Yi; Zhao, Bi; Shang, Huifang (Frontiers in Aging Neuroscience, 2023)
Background The 2008 criteria for the diagnosis of multiple system atrophy (MSA) has been widely used for more than 10 years, but the sensitivity is low, particularly for patients in the early stage. Recently, a new MSA diagnostic criteria was developed. Objective The objective of the study was to assess and compare the diagnostic utility of the new movement disorder society (MDS) MSA criteria with the 2008 MSA criteria. Methods This study included patients diagnosed with MSA between January 2016 and October 2021. All patients underwent regular face-to-face or telephonic follow-ups every year until October 2022. A total of 587 patients (309 males and 278 females) were retrospectively reviewed to compare the diagnostic accuracy of the MDS MSA criteria to that of the 2008 MSA criteria (determined by the proportion of patients categorized as established or probable MSA). Autopsy is the gold standard diagnosis of MSA, which is not available in clinical practice. Thus, we applied the 2008 MSA criteria at the last review as the reference standard. Results The sensitivity of the MDS MSA criteria (93.2%, 95% CI = 90.5–95.2%) was significantly higher than that of the 2008 MSA criteria (83.5%, 95% CI = 79.8–86.6%) (P < 0.001). Additionally, the sensitivity of the MDS MSA criteria was maintained robustly across different subgroups, defined by diagnostic subtype, disease duration, and the type of symptom[s] at onset. Importantly, the specificities were not significantly different between the MDS MSA criteria and the 2008 MSA criteria (P > 0.05). Conclusion The present study demonstrated that the MDS MSA criteria exhibited good diagnostic utility for MSA. The new MDS MSA criteria should be considered as a useful diagnostic tool for clinical practice and future therapeutic trials.